2018
DOI: 10.1126/science.aat7228
|View full text |Cite
|
Sign up to set email alerts
|

Ancient steroids establish the Ediacaran fossilDickinsoniaas one of the earliest animals

Abstract: The enigmatic Ediacara biota (571 million to 541 million years ago) represents the first macroscopic complex organisms in the geological record and may hold the key to our understanding of the origin of animals. Ediacaran macrofossils are as “strange as life on another planet” and have evaded taxonomic classification, with interpretations ranging from marine animals or giant single-celled protists to terrestrial lichens. Here, we show that lipid biomarkers extracted from organically preserved Ediacaran macrofo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
92
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 202 publications
(101 citation statements)
references
References 50 publications
4
92
0
2
Order By: Relevance
“…Similar to previously described growth patterns (Evans et al, 2017), muscles and bilateral symmetry are not found in modern placozoans (Botting, Yuan, & Lin, 2014;Finnerty, 2005;Steinmetz et al, 2012). Placozoans change dramatically in size and shape as they move (Pearse, 1989) (Bobrovskiy et al, 2018). Our data further support placement of Dickinsonia within an extinct eumetazoan clade that utilized gene regulatory networks common to all animals to produce complex, bilaterian grade body organization (Bobrovski et al, 2019;Erwin, 2009;Erwin & Davidson, 2002;Evans et al, 2017;Tweedt & Erwin, 2015).…”
Section: Phylogenetic Interpretationsupporting
confidence: 88%
See 2 more Smart Citations
“…Similar to previously described growth patterns (Evans et al, 2017), muscles and bilateral symmetry are not found in modern placozoans (Botting, Yuan, & Lin, 2014;Finnerty, 2005;Steinmetz et al, 2012). Placozoans change dramatically in size and shape as they move (Pearse, 1989) (Bobrovskiy et al, 2018). Our data further support placement of Dickinsonia within an extinct eumetazoan clade that utilized gene regulatory networks common to all animals to produce complex, bilaterian grade body organization (Bobrovski et al, 2019;Erwin, 2009;Erwin & Davidson, 2002;Evans et al, 2017;Tweedt & Erwin, 2015).…”
Section: Phylogenetic Interpretationsupporting
confidence: 88%
“…While the exact method of feeding is difficult to illustrate, the fact that Dickinsonia seems to have actively degraded the organic mat over its entire bottom surface is inconstant with a crown‐group bilaterian placement, as these organisms almost exclusively feed via an oral opening (mouth). Recent analysis of lipid biomarkers in organically preserved Dickinsonia from Russia suggests that it produced cholesteroids, indicative of a metazoan affinity (Bobrovskiy et al, ). Our data further support placement of Dickinsonia within an extinct eumetazoan clade that utilized gene regulatory networks common to all animals to produce complex, bilaterian grade body organization (Bobrovski et al, ; Erwin, ; Erwin & Davidson, ; Evans et al, ; Tweedt & Erwin, ).…”
Section: Implications For Dickinsoniamentioning
confidence: 99%
See 1 more Smart Citation
“…Geological context of Ediacaran deposits of the White Sea area. Due to the mild thermal history of Ediacaran deposits in the White Sea area, Ediacaran macrofossils co-occur there with extremely well preserved biomarkers 22,23 , offering a unique opportunity to assess the habitat and ecological preferences of these problematic organisms. The White Sea area offers localities with the most diverse and abundant Ediacara biota in the world, including various members of the White Sea, Avalon and Nama assemblages [24][25][26][27] .…”
Section: Resultsmentioning
confidence: 99%
“…Peak areas are uncorrected for differences in GC-MS response. Quantification errors were calculated as a function of a peak area established for the GC-MS used in this study 22 .…”
Section: Methodsmentioning
confidence: 99%